Tinjauan Pustaka: Miskonsepsi dan Metode Identifikasinya - Aulia, Rahma Nurul; Yogica, Relsas; Fadilah, Muhyiatul; Fajrina, Suci (Lembaga Yasin AlSys, 2024)
Misconception is a misunderstanding of someone in connecting one concept with another concept, between a new concept and a concept that is in the minds of students, which forms a wrong concept and is contrary to the conception of previous experts. After the researcher identified the previous articles, it was found that misconceptions must be corrected and overcome so as not to affect the understanding of further students. There are several methods that can overcome misconceptions, namely by using tests with certainty techniques (CRI), tests with isomorphic techniques, with diagnostic tests three tier, and with diagnostic tests four tier.